Compounding Privilege, Resilience, and Nonmedical Prescription Stimulant Use among College Students. (15th October 2022) - Holm, Abby K. Johnson; Tuthill, Shelby D.; Klein, Neelamberi D.; Wedell, Emma; Looby, Alison; Bravo, Adrian J.; Prince, Mark A.; ,
Abstract: Background : In this study, we examined why non-Hispanic White cisgender men are more likely than other subgroups to misuse prescription stimulants in college. The objective of the current study was to use a strength-based framework to examine intersectional demographic predictors. Methods : We examined gender and race/ethnicity as predictors of nonmedical prescription stimulant use (NPS) among college students. We also investigated resilience as a moderator. This report uses data from an online multisite study conducted at seven universities with 4, 764 undergraduate students (70.1% women and 52.0% People of Color). Results : We found that college students who were cisgender men and non-Hispanic White used NPS significantly more than students who identified as another gender and as People of Color. There was also a buffering effect of resilience between race/ethnicity and NPS, such that resilience predicted lower NPS for People of Color, but not non-Hispanic White people 28% of the time. Conclusions : It may be that Students of Color are more resilient than non-Hispanic White students, and this resilience is protective of NPS use in college. Importantly, a compounding-privilege and/or intersectional approach to identity is crucial to fully understanding behavior (in this case NPS) in a diversity of college students; future studies should continue to use and develop such approaches.